PERBEDAAN PENURUNAN CHEMICAL OXYGEN DEMAND (cod) MELALUI PEMBERIAN TAWAS DAN POLY ALUMINIUM CHLORIDE (PAC) PADA LIMMBAH CAIR RUMAH PEMOTONGAN HEWAN PENGGARON SEMARANG - Ulima Salsabila; Tri Joko; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2018)
Slaughterhouse is one of the servise providers for the provision of meat for the needs of the community that produces liquid waste containing blood, protein, fat and suspended solids that cause high organuc material. The content of organic substances (COD levels) causes a decrease in the amount of oxygen in the water and affect the life of water biota. Therefore, it is necessary to do the liquid wastewater treatment by flocculation coagulation process. The study aims to determine the difference in the decrease of alum coagulant and Poly Aluminium Chloride (PAC) with various dose variation in lowering COD levels. This type of research is a real experiment with pretest-posttest with control group design. The total samples were 36 samples which were 30 treatment samples and 6 controls. The results of the test with Kruskal Wallis on the sample before the given of alum treatment was 0,016 while the PAC was 0,197. The optimum dose of alum in reducing the COD level of liquid waste of the Animal Slaughtering House (RPH) because the result is still above the quality standard based on Provincial Regulation od Central Java No. 5 Year 2012 amounted to 200 mg/l. Therefore, furtjer handling of wastewater is required.